Aescin-induced reactive oxygen species play a pro-survival role in human cancer cells via ATM/AMPK/ULK1-mediated autophagy. (December 2018) - Li, Bin; Wu, Guo-liang; Dai, Wei; Wang, Gang; Su, Hao-yuan; Shen, Xue-ping; Zhan, Rui; Xie, Jia-ming; Wang, Zhong; Qin, Zheng-hong; Gao, Quan-gen; Shen, Gen-hai
Abstract Aescin, a natural mixture of triterpene saponins, has been reported to exert anticancer effect. Recent studies show that aescin increases intracellular reactive oxygen species (ROS) levels. However, whether the increased ROS play a role in the anticancer action of aescin remains to be explored. In this study, we demonstrated that aescin (20−80 μg/mL) dose-dependently induced apoptosis and activated mammalian target of rapamycin (mTOR)-independent autophagy in human hepatocellular carcinoma HepG2 cells and colon carcinoma HCT 116 cells. The activation of autophagy favored cancer cell survival in response to aescin, as suppression of autophagy with ATG5 siRNAs or 3-methyladenine (3-MA), a selective inhibitor of autophagy, promoted aescin-induced apoptosis in vitro, and significantly enhanced the anticancer effect of aescin in vivo. Meanwhile, aescin dose-dependently elevated intracellular ROS levels and activated Ataxia-telangiectasia mutated kinase/AMP-activated protein kinase/UNC-51-like kinase-1 (ATM/AMPK/ULK1) pathway. The ROS and ATM/AMPK/ULK1 pathway were upstream modulators of the aescin-induced autophagy, asN -acetyl-l -cysteine (NAC) or ATM kinase inhibitor (KU-55933) remarkably suppressed aescin-induced autophagy and consequently promoted aescin-induced apoptosis, whereas overexpression of ATG5 partly attenuated NAC-induced enhancement in aescin-induced apoptosis. In conclusion, this study provides new insights into the roles of aescin-mediated oxidative stress and autophagy in cancer cell survival. Our results suggest that combined administration of the antioxidants or autophagic inhibitors with aescin might be a potential strategy to enhance the anticancer effect of aescin.